ANALISIS PENGARUH INFRASTRUKTUR JALAN, LISTRIK, SEKOLAH, DAN PDRB TERHADAP KEMISKINAN DI ACEH - Shiffa Fardilla; Raja Masbar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThis study aims to analyze the effect infrastructure of road, electricity, school, and GRDP on poverty in Aceh in the period 2012 to 2017 using the fixed effect model (FEM). The regression coefficient show that the road infrastructure variable has a negative and significant on Aceh’s poverty, electricity variable has no effect on Aceh’s poverty, schools variable has a negative and significant effect on Aceh’s poverty, while GRDP variable has no effect on Aceh’s poverty. An increase in GRDP is actually very necessary but not enough to overcome the problems of poverty in Aceh Province. The results of this study are expected to be used as indicators of the government to choose policies that are suitable for reducing poverty in Aceh. Efforts to reduce poverty are even more focused because reducing the number of poor people in an area will have an impact on national development and poverty alleviation programs are expected to be affordable to all levels of society.Keywords: Poverty, Gross Regional Domestic Product (GRDP), Poor Population, Infrastructure, Fixed Effect Model